Hematological alteration in HIV patients - Taroeno, Suryo Aribowo; Mahmuda, Iin novita Nurhidayati; Nugrahaeni, Sarwasri Fajra; Torizal, Fuad Gandhi (JHeS (Journal of Health Studies), 2024)
HIV is a global health problem still challenging in almost all parts of the world, including Indonesia. HIV AIDS cases in Indonesia continue to increase from year to year. HIV is characterized by a progressive decline in the immune system that contributes to the clinical progression of the disease. Hematological alterations can result from the consequences of HIV. This study aimed to determine hematologic alteration in HIV patients as a predictor of disease severity. The study design was descriptive observational with a cross-sectional approach to see hematological abnormalities in HIV patients at PKU Muhammadiyah Surakarta Hospital. This study produced data that hematological alterations found include anemia in 60% of HIV patients, with the most cases being mild anemia. A small percentage of HIV patients experience leukopenia and thrombocytopenia, which are as much as 8% and 12%. HIV-positive patients have at least one or more cytopenia. Thus, hematologic alteration can independently predict morbidity and mortality and is associated with disease progression and even death.